Google maps in the meaningful teaching of geography in primary students. - Samir Enrique Barrios Gamez (REDIELUZ, 2024)
The educational resource Google Maps, its appropriate and oriented use guarantees an optimal educational process, since it promotes encounters of primary students with their local, regional, national and international reality from the application of a cartographic tool, proposing cognitive spaces to observe, describe, compare, analyze and solve multiple contemporary problems. The general objective of this research is to describe the benefits of using Google Maps in the meaningful teaching of geography to primary school students. The research was documentary type, retrospective, articles published before 2018 and inclusion above this date were taken as exclusion criteria. Technological advances have progressively penetrated the educational sphere, incorporating emerging technological resources that seek to improve teaching and learning processes. ICTs applied to the world of geography today involve massive dissemination of spatial images and development of analysis and knowledge techniques.